In-Plane Interactive Buckling of High Strength Steel Welded Wide Web I-Section Beam-Columns - Pei Xin Liang; Bin Huang (Advances in Materials Science and Engineering)
A numerical investigation on the overall-local interactive buckling performance of high strength steel (HSS) wide web I-section members was conducted using finite element (FE) models verified against experimental data. The effect of overall slenderness, the height-thickness ratio of the web hw/tw, and the width-thickness ratio of the flanges (bf/tf) on ultimate load was parametrically analyzed. The result demonstrated that (i) for the beam-columns with higher steel grade, the Pz-Uz curve presents a relatively obvious deformation plateau, meaning a certain degree of ductility. (ii) The ultimate load decreased essentially linearly resulting from higher hw/tw, and the trend was graphically consistent under various steel grades. (iii) bf/tf lower than 0.6 led to the failure mode of shearing buckling, and the corresponding ultimate load increased with an increase of bf/tf. In the case of bf/tf greater than 0.6, the ultimate load decreased as a result of the higher bf/tf. Based on the concept of the direct strength method, the local postbuckling strength prediction formula was fitted with stub beam-column FE results and examined with experiment data. The correlation formula of compression and bending moment was proposed to evaluate the resistance of the interactive buckling of the HSS wide web I-section underpinned by the FE results of beam-columns with intermediate length and experiment data.